O valente pole dance: gênero, corpo e resistência na comunidade pole dancer - Silva, Julia do Carmo da (2023)
This study conducted an ethnography in a Pole Dance studio in a municipality in the interior of Rio Grande do Sul, aiming to answer the central question "How are gender and body issues addressed within pole dance and what role do images play in this process?" The main goal was to analyze the role of images within the practice, linked to the use of the interlocutors and their presence on social media, exploring how the predominantly feminine modality sparks debates about gender, as well as understanding the role of the pole dancer's body, seeking to grasp how it is constructed and how it is perceived within the modality and by those who practice it. The specific objectives aimed to identify, based on the interlocutors' statements and the conducted analyses, how women comprehend the impact of pole dance on their lives, how it affects their self-perception, and how the pole dance addresses diversity issues. For this purpose, in addition to participant observation ethnography, interviews and analyses of social media were conducted (FONSECA, 2000; HINE, 2015, 2020; BRITES, MOTTA, 2017). As demonstrated throughout the study, based on field findings, the centrality of images (MILLER, 2019, 2022; GOMEZ, LEITÃO, 2017) within the modality was highlighted, primarily through their constant presence on the interlocutors' social media and the importance of photos during classes and in the pole dancers' evolution process. Performance (DAWSEY ET AL, 2013) also plays a significant role, aiding in the understanding of the construction of this pole dancer's body, achieved through specific rituals, and following designated training and rules, both during presentations and interactions in classes and beyond. A body that is constructed and modified through affection, something evident in the interlocutors' discourse. Pole dance also becomes a space of possibilities for discussing gender and sexuality by offering a safe environment where practitioners can share their fears and insecurities, in an atmosphere of solidarity and agency possibilities, transforming women's relationship with themselves, their bodies, and their surroundings (BUTLER, 2003) (SCOTT, 1995). It also provides a space that embraces body diversities and allows for new perspectives on them.